# Isentropic flow relations

(Difference between revisions)
 Revision as of 21:41, 3 September 2005 (view source)Jola (Talk | contribs)m (Iseptropic Flow Relations moved to Isentropic Flow Relations)← Older edit Revision as of 12:08, 5 September 2005 (view source)Jola (Talk | contribs) Newer edit → Line 12: Line 12: $\frac{A}{A*}=\frac{1}{M}*(\frac{\gamma+1}{2})^{\frac{-\gamma+1}{2(\gamma-1)}}*(1+\frac{\gamma-1}{2}M^2)^{\frac{\gamma+1}{2(\gamma-1)}}$ $\frac{A}{A*}=\frac{1}{M}*(\frac{\gamma+1}{2})^{\frac{-\gamma+1}{2(\gamma-1)}}*(1+\frac{\gamma-1}{2}M^2)^{\frac{\gamma+1}{2(\gamma-1)}}$ + + [[category: Equations]]

## Revision as of 12:08, 5 September 2005

$M = \frac{v}{a}$

$a = \sqrt{\gamma R T}$

$\frac{p_0}{p} = (\frac{T_0}{T})^\frac{\gamma}{\gamma - 1}$

$\frac{p_0}{p}=(1+\frac{\gamma-1}{2}M^2)^{\frac{\gamma}{\gamma-1}}$

$\frac{T_0}{T}=1+\frac{\gamma-1}{2}M^2$

$\frac{\rho_0}{\rho}=(1+\frac{\gamma-1}{2}M^2)^{\frac{1}{\gamma-1}}$

$\frac{A}{A*}=\frac{1}{M}*(\frac{\gamma+1}{2})^{\frac{-\gamma+1}{2(\gamma-1)}}*(1+\frac{\gamma-1}{2}M^2)^{\frac{\gamma+1}{2(\gamma-1)}}$